Thermo‐Responsive Multi‐Cargo Core Shell Particles. (7th November 2012) - Nollet, Maxime; Depardieu, Martin; Destribats, Mathieu; Backov, Rénal; Schmitt, Véronique
<x xml:space="preserve">Abstract</x> Combining formulation of particle‐stabilized water‐in‐oil‐in‐water emulsion and in situ sol‐gel chemistry, original monodisperse thermo‐responsive capsules able to encapsulate at once hydrophilic and hydrophobic drugs are synthesized. Due to the presence of a stiff shell, the release is provoked by increasing the temperature above the wax melting point. The solid‐to‐liquid transition induces a volume expansion responsible for the capsule rupture. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>